The Relationship Between Service Quality and Costs to Patient Loyalty - Permatasari, Haena; Purnomo, Muhammad; Mardiana, Sri Siska (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to determine the relationship between service quality and service costs on patient loyalty at the Ibnu Sina Jepara Primary Clinic. The specific objectives include evaluating the levels of service quality, cost perception, and patient loyalty, as well as analyzing the strength of their relationships. Research Method: A quantitative approach was employed using an analytical survey with a cross-sectional design. The total sample comprised 78 respondents, selected using the Slovin formula from a population of 350 outpatient general service patients. Data were collected through a structured questionnaire measuring service quality, service cost, and patient loyalty. The validity and reliability of the instruments were ensured by referring to previously tested instruments. Univariate and bivariate analyses were conducted, with Spearman's correlation used to assess relationships between variables. Results and Discussion: The results indicate that both service quality and service cost have significant relationships with patient loyalty. High perceptions of service quality and higher cost acceptance were associated with stronger patient loyalty. The study confirms the theoretical assumptions that perceived value—reflected in quality and price—plays a crucial role in determining loyalty in healthcare services. Implications: Findings suggest that clinics must enhance service quality while maintaining transparent and value-based pricing to foster greater patient loyalty. These results can inform clinic management strategies focused on quality improvement and cost efficiency.